2021
DOI: 10.21037/jtd-21-617
|View full text |Cite
|
Sign up to set email alerts
|

Surgery without preoperative histological confirmation of lung cancer: what is the current clinical practice?

Abstract: Background: There are discordances in the guidelines regarding the need to acquire histological diagnosis before surgical treatment of (presumed) lung cancer. Preoperative histological confirmation is always encouraged in this setting to prevent unnecessary surgery or when sublobar resection for small-sized tumors is considered. The aim of this retrospective cohort study was to assess the proportion of patients undergoing lung cancer resection in the Netherlands without preoperative pathological confirmation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…These results are consistent with the idea that it is possible to obtain a safe indication in a completely non-invasive way, without proceeding to a pre-surgical biopsy or an avoidable resection. This in line with studies such as that of Ghamati et al, who showed that it is common practice to carry out a lung resection without a preoperative defined diagnosis, risking an increase in the rates of unnecessary surgery [34]. The physician's ability to make a reliable lung cancer diagnosis solely based on clinical and radiologic data in fact represents an undeniable challenge.…”
Section: Discussionsupporting
confidence: 65%
“…These results are consistent with the idea that it is possible to obtain a safe indication in a completely non-invasive way, without proceeding to a pre-surgical biopsy or an avoidable resection. This in line with studies such as that of Ghamati et al, who showed that it is common practice to carry out a lung resection without a preoperative defined diagnosis, risking an increase in the rates of unnecessary surgery [34]. The physician's ability to make a reliable lung cancer diagnosis solely based on clinical and radiologic data in fact represents an undeniable challenge.…”
Section: Discussionsupporting
confidence: 65%
“…In a study of 10,226 patients in Netherlands who underwent surgical resection for lung cancer, more than one-third of the patients were operated without preoperative diagnosis. 29 Not all nodules are amenable to preoperative tissue sampling, either because of size or location, and contraindications to biopsy, such as severe emphysema and pulmonary hypertension. The method and results of the percutaneous biopsy are also operator and technique dependent.…”
Section: Discussionmentioning
confidence: 99%
“…1). Diagnostic lobectomy or segmentectomy is commonly performed and usually does not lead to major complications [8,9]. The proportion of pulmonary nodules determined to be cancer in biopsy results varies greatly depending on their size and shape [10,11].…”
Section: Introductionmentioning
confidence: 99%